2021
DOI: 10.1016/j.jcmgh.2021.06.013
|View full text |Cite
|
Sign up to set email alerts
|

PIR-B Regulates CD4+ IL17a+ T-Cell Survival and Restricts T-Cell–Dependent Intestinal Inflammatory Responses

Abstract: The inhibitory receptor paired immunoglobulin-like receptor B regulates CD4 þ T-helper 17 cell-dependent chronic intestinal inflammatory responses by tempering mammalian target of rapamycin complex Q8 1 signaling and enhancing CD4 þ interleukin 17a þ T-cell survival and regulates the outgrowth and maintenance of tissue resident memory CD4 þ interleukin 17a þ T cells.BACKGROUND & AIMS: CD4 þ T cells are regulated by activating and inhibitory cues, and dysregulation of these proper regulatory inputs predisposes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 88 publications
(103 reference statements)
0
5
0
Order By: Relevance
“…Its loss of function inhibited the differentiation and growth of CD4 + IL17A + T RM cells, thus protecting against the development of CD4 + T cell-dependent colitis in a T cell transfer mouse model. 110 These studies showed that the number of T RM cells in the intestines of patients with IBD increased, and that they had a stronger pro-inflammatory capacity. This may be due to the regulation of transcription factors, such as Eomes.…”
Section: Increased Number and Enhanced Ability Of Pro-inflammatory T ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Its loss of function inhibited the differentiation and growth of CD4 + IL17A + T RM cells, thus protecting against the development of CD4 + T cell-dependent colitis in a T cell transfer mouse model. 110 These studies showed that the number of T RM cells in the intestines of patients with IBD increased, and that they had a stronger pro-inflammatory capacity. This may be due to the regulation of transcription factors, such as Eomes.…”
Section: Increased Number and Enhanced Ability Of Pro-inflammatory T ...mentioning
confidence: 99%
“…Similarly, the paired immunoglobulin‐like receptor B intrinsically regulates CD4 + IL17A + T cell survival. Its loss of function inhibited the differentiation and growth of CD4 + IL17A + T RM cells, thus protecting against the development of CD4 + T cell‐dependent colitis in a T cell transfer mouse model 110 …”
Section: Trm Cells In Inflammatory Bowel Diseasementioning
confidence: 99%
“…Our previous study identified a direct interaction between ANGPTL8 and the PIRB receptor [ 16 ], which corresponds to LILRB2 in humans [ 40 ]. LILRB2/PIRB is an inhibitor of inflammation and autoimmunity [ 41 ], and LILRB2 blockade with antagonizing antibodies increases tumor cell death and the killing activity of cytotoxic T lymphocytes [ 20 ]. We found that ANGPTL8 colocalized with LILRB2/PIRB on the cell membrane, and a chimeric receptor assay confirmed a direct interaction between them.…”
Section: Discussionmentioning
confidence: 99%
“…The mice were weighed every 5 days after transfer. The clinical score was graded on a scale of 0 to 5 and was based on decreased activity, hunched posture, ruffled fur, rate of breathing, shrunken eyes, shivering, rectal bleeding, and diarrhea as previously described ( 65 , 66 ). The mice were euthanized on day 45 after transfer, and the colons were collected for measurement of length and histological analysis.…”
Section: Methodsmentioning
confidence: 99%